Quitting livestock farming: transfarmation pathways and factors of change from post-livestock farmers’ accounts - Salliou, Nicolas (Frontiers in Sustainable Food Systems, 2023)
Transitioning away from livestock farming would limit the carbon footprint of humanity and reduce the pressure on water, land and biodiversity. It would also improve human health, as animal farming increases the risks of pandemics and bacterial resistance. All of these risks and opportunities make a compelling case for a transition towards plant-based diets. In case of a large-scale transition, hundreds of thousands of farmers would have to quit animal farming and switch to other activities. Such transition is potentially happening in developed countries, where industrial operations are located, consumption per capita is the highest and alternatives to animal products are increasingly available. However, there is considerable resistance from farmers to this transition. There is thus a need to better understand potential transition pathways to support smooth transitions. To do so, 27 stories of farm transitioning out of livestock farming – so called transfarmation - were collected. Most of these cases are located in Switzerland and the US. These accounts were published on the websites of organizations that support farmers transitioning out of livestock production or by farmers themselves. In this qualitative study, I coded these accounts to identify patterns in the drivers, behaviour and decision-making of farmers explaining their transition. Two main patterns were identified: (1) transfarmations from intensive poultry or pig farms towards a mushroom or market gardening farm, driven by economic interests and (2) transfarmations driven by compassion to animals, mostly leading to a farmed animal sanctuary or market gardening farm. Support organizations for transfarmation seem to be particularly beneficial for the second type of transition. I conclude this paper with research perspectives on the topic of transfarmation, especially on the role of gender and the potential of transfarmation for the green care economy.